(untitled) (International Journal of Natural Sciences, 2012)
The present study was undertaken to investigate the adaptability and survivability of different crossbred dairy cows under commercial farming conditions in Chittagong, Bangladesh. Different cattle genotypes (Holstein × Local, Sahiwal × Local, Sahiwal × Holstein and Jersey × Local) were found in the studied farms. The percentages of Holstein × Local was (58.94%) higher than other genotype. The survivability of Holstein × Local, Sahiwal × Local, Sahiwal × Holstein and Jersey × Local calves were 84.0±3.90, 100, 97.1±5.48 and 100 percent, respectively. The survivability of calves and cows were significantly different (P<0.05) among genotype. Survivability of bull-calves and heifers were similar for all the genotypes. International Journal of Natural Sciences (2012), 2(3):67-70 DOI: http://dx.doi.org/10.3329/ijns.v2i3.12134